Synthesis of Graphene Aerogel for Adsorptive Removal of Tetracycline from Water: Impact of Operating Parameters - Trinh, Tran Dinh; Noi, Nguyen Van; Tuan, Bui Anh (VNU Journal of Science: Natural Sciences and Technology; Vol 39 No 4DO - 10.25073/2588-1140/vnunst.5615, 2023)
Graphene aerogel (GA) was synthesized by chemical reduction of graphene oxide (GO) using ethylene diamine as a reducing agent, which was then followed by a freeze-drying process. The morphology and surface properties of GA, GO samples were characterized by Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), Scanning electron microscopy (SEM), Energy-dispersive X-ray spectroscopy (EDX), and Brunauer-Emmett-Teller (BET). GA was then used to study the adsorption process of tetracycline (TC) in aqueous solutions. Different parameters influencing the adsorption efficiency of GA such as pH, adsorbent load, initial concentration of TC, contact time were investigated. The results showed that when GO was transformed to GA, the XRD characteristic peak at about 10.8˚ was shifted to broad peaks at 26˚ and 43˚, implying that the crystalline structure of GO was converted to GA which contained a large percent of amorphous structure and a smaller crystalline structure formed by stacking layers of graphene. The C/O ratio in GA sample was significantly increased compared to GO samples (6.5/1 compared to 1.38/1), suggesting that oxygen-containing functional groups (-OH, -C=O, -O-…) in GO were drastically reduced. The optimal conditions for the adsorption of TC were 10 mg L -1 TC solution, pH 7.0 at 75 min, 0.1 g L -1 of adsorbent, and at 30 °C. The adsorption process was better described by Langmuir isotherm model (R 2 =0.9938) compared to Freundlich one (R 2 =0.1302). The maximum adsorption capacity (Q max ) of GA calculated by the Langmuir model was 107.5 mg g -1 , significantly higher than other common adsorbents. GA presented a stable and promising adsorbent for TC removal in water.